Proteus mirabilis biofilm - Qualitative and quantitative colorimetric methods-based evaluation - Kwiecinska-Piróg,Joanna (2014)
Proteus mirabilis strains ability to form biofilm is a current topic of a number of research worldwide. In this study the biofilm formation of P. mirabilis strains derived from urine of the catheterized and non-catheterized patients has been investigated. A total number of 39 P. mirabilis strains isolated from the urine samples of the patients of dr Antoni Jurasz University Hospital No. 1 in Bydgoszcz clinics between 2011 and 2012 was used. Biofilm formation was evaluated using two independent quantitative and qualitative methods with TTC (2,3,5-triphenyl-tetrazolium chloride) and CV (crystal violet) application. The obtained results confirmed biofilm formation by all the examined strains, except quantitative method with TTC, in which 7.7% of the strains did not have this ability. It was shown that P. mirabilis rods have the ability to form biofilm on the surfaces of both biomaterials applied, polystyrene and polyvinyl chloride (Nelaton catheters). The differences in ability to form biofilm observed between P. mirabilis strains derived from the urine of the catheterized and non-catheterized patients were not statistically significant.